The Influence of Religious Motivation, Physics Learning Motivation on The Results of Basic Physics Learning of Physics Education Students - Murtono, Murtono (Proceeding International Conference on Religion, Science and Education, 2023)
Student learning outcomes are influenced by many factors, including motivation. With motivation a person has the drive to do something for the better. This study aims to determine the partial or joint influence between learning motivation and religious motivation on the learning outcomes of physics education students. Data collection with motivation questionnaires and learning outcomes tests during lectures in one semester. Teknik analysis of research data, using multiple linear regression analysis and the results obtained the magnitude of the correlation coefficient R, the coefficient of determination R2, the partial correlation coefficient and the contribution of each motivation towards student learning outcomes. The results showed that there was a significant correlation together between religious motivation and motivation to learn physics with the results of learning physics shown by the price of the correlation coefficient R = 0.430 and the coefficient of determination R2= 0.185. The effective contribution of religious motivation to physics learning outcomes was 0.138% and the effective contribution of motivation to learn physics was 0.859%. There is a significant influence of religious learning motivation and physics learning motivation on physics learning outcomes together.